Bufonis venenum extract loaded novel cholesterol-free liposome for the treatment of hepatocellular carcinoma - Yang, Siqi; Lan, Jinshuai; Li, Zhe; Li, Ming; Wu, Ya; Sun, Liyan; Zhang, Tong; Ding, Yue (Frontiers in Pharmacology, 2024)
Background: This study aims to improve the solubility and the toxicity of Bufonis venenum, and finally enhance the therapeutic outcomes of hepatocellular carcinoma (HCC). Methods: The cholesterol-free liposomes simultaneously encapsulate bufadienolides and indolealkylamines (Non-Cholesterol-Bufonis Venenum Extract-Liposome, Non-Chol-BVE-LP) was prepared by the thin-film evaporation technique. In vitro, the cytotoxicity, cell apoptosis study, cellular uptake and hemolysis studies were evaluated in HepG2 cells. In vivo, the biodistribution and anti-tumor activity studies were conducted in BALB/C mice with HepG2 cells. Results: The liposome showed good size distribution, encapsulation efficiency drug loading capacity and slower drug release. Non-Chol-BVE-LP had higher cytotoxicity on HepG2 cells and induced more apoptosis on HepG2 cell compared with BVE. In addition, the liposomes could accumulate in tumor by passive targeting, thus facilitating the anti-tumor effects. In vivo, Non-Chol-BVE-LP showed equivalent anti-tumor efficacy to the first-line anti-HCC drug sorafenib. Conclusions: The study provided new ideas for the development and clinical application of Bufonis venenum related formulation and offered new drug for the treatment of HCC.